(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Health insurance has become one of the primary modes of payment for healthcare services. Even though general health insurance has advanced significantly, it is still not comprehensive. Dental insurance is almost non-existent in India. Teeth and gums are as important as other vital organs in the human body. In India, more than 85% of the population has poor oral health. Despite this, only 12.4% of adults go to the dentist to get their teeth checked out and fixed. The cost of dental treatment is one of the major reasons people avoid visiting a dentist. In India, very few insurance companies cover dental insurance, and these are also insufficient. Therefore, dental insurance is the need of the hour. This article focuses on the current scenario of dental insurance in India.